Translating an Oriental Frame Tale and its Translator in Hapsburg Spain: The Prefaces to the Espejo político y moral (1654, 1659). Issue 7 (July 2020) - SCOTT, RACHEL
Abstract : In comparison with earlier, medieval translations of Kalila wa-Dimna, such as the well-known Calila e Dimna (1251) or the Exemplario contra los engaños y peligros del mundo (1483), the version composed by Vicente Bratutti from a sixteenth-century Turkish source, the Espejo político y moral para príncipes y ministros y de todo género de personas (1654, 1659), has been the focus of much less scholarship. Yet, as I will argue, it is worthy of critical attention, above all for the ideological richness of the prefaces written by the translator and censors, which provide differing and often contrasting perspectives on both this famous Eastern work and Spain's position in the world and relations with other powers. This article examines how the fables were framed by Bratutti and the censors for new audiences, and how their relevance for the Spanish monarchy was justified. It considers the representation of translatio studii et imperii ; and it looks at how its Ragusan translator was himself 'translated' by the Inquisition's censors for seventeenth-century Spanish audiences.